Exploring the impact of telemedicine in chronic patients from diverse socioeconomic contexts: systematic review of qualitative studies - Li, Yuzhe; Shi, Qifang; Yang, Jing; Ran, Li (Frontiers in Public Health, 2025)
BackgroundTelemedicine has a positive impact on improving health literacy and disease management ability of chronic disease patients and reducing the medical burden. However, telemedicine still has many problems in chronic disease management. We should actively solve the problems and maximize the functions of telemedicine.ObjectiveTo explore the application and improvement of telemedicine in chronic disease self-management to provide important insights from functional module analysis for stakeholders, healthcare professionals, and policymakers to promote the development of telemedicine in chronic disease management.DesignWe conducted a systematic review and qualitative synthesis of five English databases including PubMed, Embase, Web of Science, Cochrane Database of Systematic Reviews, and Scopus, as well as three Chinese databases: China National Knowledge Infrastructure (CNKI), WanFang and VIP database. Databases were searched from inception until November 12, 2024.MethodsThis review is reported in accordance with guidelines for Enhancing Transparency in Reporting the Synthesis of Qualitative Research (ENTREQ). Two reviewers independently performed study selection, data extraction, and quality assessment using the Joanna Briggs Institute's key assessment tools for qualitative research. Thematic analysis was used for data synthesis.ResultsA total of 35 studies were included, and the contents were refined and summarized into 8 new subthemes. Then, four themes were synthesized: Reminder and supervisor, Access to knowledge, Transition in medical treatment mode, and Emotional support platform.ConclusionBy improving information quality, developing diverse functions, and constructing multidisciplinary coordination mechanisms to meet the needs of patients with chronic diseases, improve the medical service system, maximize the function of telemedicine, and enhance the stickiness of patients to use telemedicine.